Myokines in Myogenesis and Health - Henriksen, Tora; Green, Charlotte; Klarlund Pedersen, Bente (Recent Patents on Biotechnology, 2012)
Although some myokines exert their actions on other organs in a hormone-like fashion, many of them operate locally on skeletal muscle themselves. Myokines may thereby provide a feedback loop for the muscle to regulate its own growth and regeneration allowing for adaptation to exercise training. The myokine concept provides a conceptual basis and a whole new paradigm for understanding how muscles communicate with other organs within the muscle itself. New biotechnological patents are published based on the identification of new myokines, and these myokines and their receptors will potentially serve as pharmacological targets for treating muscle diseases, metabolic disorders and other diseases associated with muscle disuse.
Keywords: Skeletal muscle